Clearance of plasma PCSK9 via the asialoglycoprotein receptor mediated by heterobifunctional ligands. Issue 1 (19th January 2023) - Bagdanoff, Jeffrey T.; Smith, Thomas M.; Allan, Martin; O'Donnell, Peter; Nguyen, Zachary; Moore, Elizabeth A.; Baird, Jason; Wang, Shuangxi; Subramanian, Vanitha; Tigani, Bruno; Nettleton, David O.; Monovich, Lauren G.; et al.
Summary: Proprotein convertase subtilisin/kexin type 9 (PCSK9) regulates plasma low-density lipoprotein cholesterol (LDL-C) levels by promoting the degradation of hepatic LDL receptors (LDLRs). Current therapeutic approaches use antibodies that disrupt PCSK9 binding to LDLR to reduce circulating LDL-C concentrations or siRNA that reduces PCSK9 synthesis and thereby levels in circulation. Recent reports describe small molecules that, like therapeutic antibodies, interfere with PCSK9 binding to LDLR. We report an alternative approach to decrease circulating PCSK9 levels by accelerating PCSK9 clearance and degradation using heterobifunctional molecules that simultaneously bind to PCSK9 and the asialoglycoprotein receptor (ASGPR). Various formats, including bispecific antibodies, antibody-small molecule conjugates, and heterobifunctional small molecules, demonstrate binding in vitro and accelerated PCSK9 clearance in vivo . These molecules showcase a new approach to PCSK9 inhibition, targeted plasma protein degradation (TPPD), and demonstrate the feasibility of heterobifunctional small molecule ligands to accelerate the clearance and degradation of pathogenic proteins in circulation. Graphical abstract: Highlights: ASGPR-targeting heterobifunctional molecules lead to the clearance of PCSK9 in vivo PCSK9 is cleared by bispecific antibodies, antibody conjugates, and small molecules PCSK9 clearance requires binding to both the ASGPR and to PCSK9 Heterobifunctional molecules do not lead to significant degradation of LDLR or ASGPR Abstract : Bagdanoff et al. describe heterobifunctional molecules that mediate in vivo clearance of the pathologically relevant plasma protein PCSK9 in mice, demonstrating rapid, ASGPR-dependent clearance using multiple classes of heterobifunctional constructs including bispecific antibodies, antibody-drug conjugates, and small molecules.